PEDAGOGICAL-PSYCHOLOGICAL FEATURES OF THE PROCESS OF DEVELOPING STUDENTS' PROFESSIONAL COMPETENCE BASED ON AN INDIVIDUAL APPROACH (Web of Teachers: Inderscience Research, 2025)
This article analyzes the pedagogical and psychological features of an individual approach in the process of developing students' professional competence. The mechanisms for implementing an individual approach in education, the importance of taking into account the personal characteristics and professional needs of students, are highlighted. Also, the possibilities of forming professional skills in students through the use of modern pedagogical technologies and increasing motivation are indicated.